Why are some people not socially distancing during COVID-19? A segmentation study. Issue 2 (4th February 2021) - Arli, Denni; Ang, Tyson; Wei, Shuqin
Abstract : Purpose: Governments around the world have used social distancing methods to slow the spread of COVID-19. Some people, however, have ignored repeated warnings about the need to maintain social distance. The purpose of this study was to segment individuals based on their perceptions of social distancing with respect to shared constructs, such as attitudes and demographic profiles. The findings can assist social marketing efforts to target specific groups for health campaigns. Design/methodology/approach: This study used a priori methods, meaning that the type and number of segments were determined in advance. Amazon's Mturk was used to collect data from an online sample of US residents ( n = 759) in May 2020, in the midst of the COVID-19 pandemic. Findings: Individuals' perceptions of social distancing were segmented as follows: Segment 1 = majority social distancing followers; Segment 2 = social distancing inbetweeners; and Segment 3 = minority social distancing rebels. Interestingly, some of these segments were strongly affiliated with political parties. In addition, the results show attitudes toward social distancing appear to be influenced by individuals' beliefs regarding their susceptibility to coronavirus and the potential severity of the symptoms or disease's impact on their lives. Research limitations/implications: This study makes several theoretical and practical contributions to the literature on these issues. In particular, it involved the application of the health belief model to the context of attitudes toward social distancing, which were found to be influenced by individuals' beliefs regarding whether they are susceptible to coronavirus infection and whether the symptoms or disease could have a significant effect on their lives. Practical implications: The results of this study will assist public health researchers, social marketers and policymakers in efforts to improve the effectiveness of health campaigns. Public health campaigns in the USA need to be bi-partisan. The finding that the social distancing rebels were mostly Republicans is consistent with an earlier report that those who identify with this party were less convinced than those who identified with the Democratic party regarding the efficacy of maintaining social distancing measures and more concerned about the adverse effects of these measures on the economy. Originality/value: Only a few studies have segmented populations based on their perceptions of social distancing. This study was designed to understand the distinguishing features of such segments to enhance health messaging and content and convince those reluctant to engage in social distancing to view the issue from the perspective of marketing and medical practitioners.